2015
DOI: 10.1103/physrevc.91.025804
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy proton capture reactions in the mass region 55–60

Abstract: Low energy proton capture reactions in the mass 55-60 region are studied in a microscopic optical model. Nuclear density profile is calculated using the relativistic mean field theory. The DDM3Y interaction is folded with the theoretical density to obtain the proton-nucleus optical potential. A definite set of normalization parameters has been obtained for the concerned mass region by comparing with all available experimental data in this mass region. These parameters have been used to obtain proton capture ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…DDM3Y interaction has been used in various works [24,25] over a wide energy range from few keV to several MeV. We have applied this optical-model potential in several of our previous works [26][27][28][29][30][31][32][33]. It is found that this semi-microscopic potential is well-capable of describing proton capture (p, γ) reaction rates over a wide mass region when real and imaginary potential well depths are being normalized with available experimental measurements [5,27,29,[31][32][33].…”
Section: B Microscopic Statistical Model Approach For Cross-section C...mentioning
confidence: 99%
See 1 more Smart Citation
“…DDM3Y interaction has been used in various works [24,25] over a wide energy range from few keV to several MeV. We have applied this optical-model potential in several of our previous works [26][27][28][29][30][31][32][33]. It is found that this semi-microscopic potential is well-capable of describing proton capture (p, γ) reaction rates over a wide mass region when real and imaginary potential well depths are being normalized with available experimental measurements [5,27,29,[31][32][33].…”
Section: B Microscopic Statistical Model Approach For Cross-section C...mentioning
confidence: 99%
“…We have applied this optical-model potential in several of our previous works [26][27][28][29][30][31][32][33]. It is found that this semi-microscopic potential is well-capable of describing proton capture (p, γ) reaction rates over a wide mass region when real and imaginary potential well depths are being normalized with available experimental measurements [5,27,29,[31][32][33]. The detailed description of the NN interaction and potential formation is given in Dutta et al [5], where we have employed this theory to calculate the (n, γ) cross sections for nuclei near N = 82 neutron shell closure.…”
Section: B Microscopic Statistical Model Approach For Cross-section C...mentioning
confidence: 99%
“…The density dependent M3Y interaction (DDM3Y), which is known to give satisfactory results in many cases, has been chosen for our purpose. Similar studies in mass region A=55-100 [8][9][10][11][12] have already been carried out and our aim is to extend this approach to A=110-125 region.…”
mentioning
confidence: 94%
“…For example, the optical potential was generated folding the nuclear density with the microscopic nuclear interaction DDM3Y to study low-energy proton reactions for different nuclei in the A ≈ 40-120 region. [31][32][33][34] In addition, the mass region ranging from A ≈ 74 to 196 is explored to calculate astrophysical Sfactor for 36 known p-nuclei with (p, γ) reactions at low energy taking spherical densities from RMF calculations. 35 On the other side, a number of studies have been completed [36][37][38] in the neighborhood of the N=82, A=130 r-process peak.…”
Section: Introductionmentioning
confidence: 99%